A cost-effective o-toulidine-based Schiff base as an efficient sorbent for metal ion uptake from aqueous and soil samples: Synthesis, antimicrobial, and acute toxicity analyses - Khan, Noureen; Jamil, Nelofer; Jabeen, Rukhsana; Akhtar, Malik Muhammad; Ali, Hussain; Mehmood, Rashad; Orfali, Raha; Perveen, Shagufta; Peng, Jiangnan; Al-Taweel, Areej M. (Frontiers in Environmental Science, 2023)
The imine derivative of the dimeric o-toulidine (SBL), has been synthesized through condensation and characterized it through modern spectroscopic techniques including 1HNMR and MS. The SBL was applied for the remediation of heavy metals Zn(II), Co(II) and Cu(II) from soil and the aqueous samples. Various factors that are influencing the metal uptake behaviour were also studied such as contact time, effect of pH (2-12), effect of initial concentration of metal (II) solutions (10-250 ppm) and effect of the amount of Schiff base ligand (0.1-2g). The equilibrium of the adsorption process was established after about 90 minutes. The heavy metals removal with SBL was found in the order of Cu+2 > Zn+2 > Co+2 for aqueous and Co+2 > Cu+2 > Zn+2 for soil samples; evaluated by the Langmuir constant (b), Freundlich intensity parameter (1/n) values, the maximum sorption capacities (qmax) and separation factor (RL). The results revealed that the adsorption percentage increases with the concentration; such trend was observed in Freundlich isotherms models, whereas in Langmuir isotherm case the maximal value of adsorption qmax value was found negative indicating its deficiency to explain the adsorption process. The modified Freundlich fitted more than the Langmuir isotherm based on R2 ranges between 90 to 100% for both aqueous and soil samples. The Schiff base was also tested for its antimicrobial potential, results revealed moderate activity against S. dysentria, C. albican and A. niger whereas weak active against S. aureus, P. aureginosa, K. pneumoniae, P. vulgaris and E.coli; using Fluconazole and Ciprofloxacin as the standard. Acute toxicity of the synthesized compound was measured through its daily oral administration with various doses 0.1-1000 mg/kg the mice body weight. Even at the dose of 1000 mg/kg of the mice; the SBL showed no mortality or any type of general behavioral change in the treated mice.